A Policia do Maranhão no começo no novo milênio: transitando entre poder, violência e luta por direitos - Teixeira, Márcio Aleandro Correia (2016)
The research The Maranhão Police in new millenium: transiting around power, violence and law aimed to evaluate the Brazilian state of policing system due to the process of institutional change brought about by the new constitutional guidelines 1988. The analysis is based on a conception of social conflict institutionalized in search of understanding an integrated policing system, able to keep up with new demands on the state in the face of conflicting dynamics of the society. The theoretical model used for the construction of research supports the significant nature of power struggles and ideological struggles for legitimacy of competitive groups of a certain institutional system.